Proceedings of the 2009 Named Entities Workshop: Shared Task on Transliteration - NEWS '09 2009
DOI: 10.3115/1699705.1699726
|View full text |Cite
|
Sign up to set email alerts
|

English to Hindi machine transliteration system at NEWS 2009

Abstract: This paper reports about our work in the NEWS 2009 Machine Transliteration Shared Task held as part of ACL-IJCNLP 2009. We submitted one standard run and two nonstandard runs for English to Hindi transliteration. The modified joint source-channel model has been used along with a number of alternatives. The system has been trained on the NEWS 2009 Machine Transliteration Shared Task datasets. For standard run, the system demonstrated an accuracy of 0.471 and the mean F-Score of 0.861. The non-standard runs yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Quite a number of transliteration mechanisms have been proposed for some non-English European languages, Russian [6][7][8] and East Asian languages like Chinese [9][10][11][12], Japanese [13][14][15][16][17], Korean [18][19][20][21][22], West Asian languages like Arabic [23][24][25] and the Persian [26,27]. There have been some recent attempts on some Indian languages like Hindi [8,[28][29][30][31][32][33][34][35][36][37][38][39], Bengali [33,[40][41][42], Punjabi [43], Telugu [44], Kannada [29,45,46] and Tamil [29,31,47]. However, the present state-of-the-art of transliteration for Indian and other South Asian languages can be considered to be in the initial stage.…”
Section: *For Correspondencementioning
confidence: 99%
“…Quite a number of transliteration mechanisms have been proposed for some non-English European languages, Russian [6][7][8] and East Asian languages like Chinese [9][10][11][12], Japanese [13][14][15][16][17], Korean [18][19][20][21][22], West Asian languages like Arabic [23][24][25] and the Persian [26,27]. There have been some recent attempts on some Indian languages like Hindi [8,[28][29][30][31][32][33][34][35][36][37][38][39], Bengali [33,[40][41][42], Punjabi [43], Telugu [44], Kannada [29,45,46] and Tamil [29,31,47]. However, the present state-of-the-art of transliteration for Indian and other South Asian languages can be considered to be in the initial stage.…”
Section: *For Correspondencementioning
confidence: 99%
“…We also note that combination of several different models via re-ranking of their outputs (CRF, Maximum Entropy Model, Margin Infused Relaxed Algorithm) proves to be very successful (Oh et al, 2009); their system (reported as Team ID 6) produced the best or second-best transliteration performance consistently across all metrics, in all tasks, except Japanese back-transliteration. Examples of other model combinations are (Das et al, 2009). At least two teams (reported as Team IDs 14 and 27) incorporate language origin detection in their system (Bose and Sarkar, 2009;Khapra and Bhattacharyya, 2009).…”
Section: Standard Runsmentioning
confidence: 99%
“…CRF on the English to Korean transliteration and Hindi-English names respectively is suggested in [17]. A transliteration scheme that involved English to Hindi language pair from news 2009 transliteration task dataset is in [18]. The methodology incorporated English and Hindi contextual information for calculating the probabilities and chose the one which has a maximum probability and further improved the algorithm by applying postprocessing rules.…”
Section: Introductionmentioning
confidence: 99%